Polycyclic Aromatic Hydrocarbons Generated by the Incomplete Combustion: Case of Fluoranthene - Belhakem, Mostefa; Derrar, Siham Naima (Int. J. Adv. Chem. Eng. Bio. Sci., 2017)
Incipient soot nanoparticles represent a real threat, due to the fatal and irreversible damages they can cause on health and environment. The incomplete combustion of engine’s fuel leads to the creation of these nanoparticles. It has been shown that they are formed by some extremely carcinogenic Polycyclic Aromatic Hydrocarbons (PAH), precisely, the aggregation of dimers and trimers and so on of PAH. Understanding the structural parameters of these aggregations is crucial to clarify the real composition of soot which remains not completely understood. This present paper is devoted to the study of the dimerization of fluoranthene. Different structural building ways have been suggested, with full and partial covering between the monomer entities. The number of the interacting six membered rings varies between one and three cycles, from each monomer. The impact of structure on both binding energy and equilibrium distance has been analyzed. Binding energies vary between -5.88 and -8.41 kcal/mol. The structural parameters seem to play a key role in the dispersion-type interactions for the fluoranthene dimers.
Keywords: Fluoranthene; Polycyclic Aromatic; Hydrocarbon; Stacking dimers; Soot